2001
DOI: 10.1046/j.1365-2958.2001.02664.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of human C4BP to the hypervariable region of M protein: a molecular mechanism of phagocytosis resistance in Streptococcus pyogenes

Abstract: The amino‐terminal hypervariable region (HVR) of streptococcal M protein is required for the ability of this virulence factor to confer phagocytosis resistance. The function of the HVR has remained unknown, but the finding that many HVRs with extremely divergent sequences bind the human complement regulator C4b‐binding protein (C4BP) has suggested that this ligand may play a role in phagocytosis resistance. We used the M22 system to study the function of bound C4BP and provide several lines of evidence that C4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
106
1
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 73 publications
(112 reference statements)
4
106
1
2
Order By: Relevance
“…This showed for the first time, to our knowledge, that CFH binding via domains 5-7 is a very important innate immuneevasion strategy for GAS. This probably was not shown previously, because the impact of CFH binding to the bacteria cannot be measured by removing CFH from serum or blood because of the resulting vigorous C activation, and removal of the M protein by bacterial mutagenesis could also impair its other functions, such as C4BP binding (40). Our approach of showing the impact of CFH acquisition for the bacteria is novel and free of these biases.…”
Section: Discussionmentioning
confidence: 93%
“…This showed for the first time, to our knowledge, that CFH binding via domains 5-7 is a very important innate immuneevasion strategy for GAS. This probably was not shown previously, because the impact of CFH binding to the bacteria cannot be measured by removing CFH from serum or blood because of the resulting vigorous C activation, and removal of the M protein by bacterial mutagenesis could also impair its other functions, such as C4BP binding (40). Our approach of showing the impact of CFH acquisition for the bacteria is novel and free of these biases.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to inhibition of the alternative pathway, several bacteria (e.g., Moraxella catarrhalis, S. pyogenes, E. coli K1, and H. influenzae) bind C4BP and are shielded against the classical and lectin pathways (49 -51). Interestingly, many species, C. albicans, Borrelia recurrentis, and S. pyogenes, among others, have been shown to bind both FH and C4BP (26,(52)(53)(54)(55). We have recently demonstrated that non-typeable H. influenzae binds C4BP (30).…”
Section: Discussionmentioning
confidence: 96%
“…Binding of FH has been demonstrated for strains of S. pyogenes (group A streptococcus) (40), Neisseria gonorrhoeae (41,42), Streptococcus pneumoniae (43)(44)(45), and Borrelia burgdorferi (46,47), while binding of C4BP has been demonstrated for strains of S. pyogenes (48 -50), Bordetella pertussis (51,52), and N. gonorrhoeae (53,54). In at least two of these cases, there is strong evidence that the bound FH or C4BP contributes to bacterial virulence (41,55). The role of the bacteria-bound RCA protein is most simply explained by its ability to down-regulate complement activation, but it also seems possible that the RCA protein contributes to virulence by mechanisms that are independent of the effect on complement activation (e.g.…”
Section: Discussionmentioning
confidence: 99%